The Impact of the E-Commerce Market on Freight Transport – The Use of Regression Analysis to Simulate Logistic Processes - Dominika KOTULSKA; Karolina TRZYNIEC; Maciej GLINIAK; Piotr WALĄG (Communications of International Proceedings, 2020)
The aim of the research was to analyze the impact of the development of the e-commerce industry on freight transport in Poland. As part of the work, the scale of interactivity of individual analyzed parameters was shown. Data from 2011-2019 were obtained to study the impact of the e-commerce industry on the transport of goods. All of the presented data describe the Polish market. The statistical analysis included the following tools: Pearson's linear correlation, least squares regression analysis, and the coefficient of determination R2. A significance test was performed for each model. The conducted research has shown that the e-commerce industry has a direct impact on the development of road transport in Poland.
Keywords: E-Commerce; Regression; Transport; Simulation.